Modulating the transcriptomic profile of multidrug-resistant Klebsiella pneumoniae biofilm formation by antibiotics in combination with zinc sulfate - Rania I. Shebl; Walid F. Elkhatib; Mona Shaban E. M. Badawy (BMC, 2023)
Abstract Background Klebsiella pneumoniae is a significant healthcare-associated pathogen. We investigated the antimicrobial interaction pattern between zinc sulfate and antibiotics against K. pneumoniae biofilm on the phenotypic and genotypic levels. Methods Determining the minimum biofilm inhibitory concentrations and the transcriptomic profile of K. pneumoniae biofilm formation genes post-treatment were carried out to evaluate the effect on the phenotypic and genotypic levels, respectively. Results Zinc enhanced the antibiofilm potentials of cephalosporins, aminoglycosides, and ertapenem, whereas it antagonizes the effectiveness of fluoroquinolones and meropenem on the phenotypic level. On the molecular level, zinc enhanced the anti-biofilm efficacies of cephalosporins (cefotaxime, ceftriaxone, ceftazidime, cefpirome, and cefepime) via down-regulating the expression of biofilm-related genes by 18-, 38-, 5-, 77- and 2-folds, respectively. Zinc in combination with aminoglycosides (kanamycin, gentamicin, and amikacin) reduced the expression of biofilm-related genes by 40-, 2602- and 20-folds, respectively, and by 2-folds in combination with ertapenem. However, a reduction in the down-regulatory potentials of fluoroquinolones was recorded following combination with zinc by 2-, 2-, 15- and 14-folds, respectively, and an up-regulation in the expression levels of the tested genes by 2-folds in the case of zinc/meropenem combination. Conclusions Results revealed variable interaction patterns between different antibiotics in combination with zinc. Current findings also shed light on the antibiofilm potentials of zinc/antibiotics combinations especially when combining zinc with fluoroquinolones or meropenem to avoid their antagonistic effects.